Healing roots : anthropology in life and medicine - Laplante, Julie (Epistemologies of healing ;, 2015)
"Umhlonyane, also known as Artemisia afra, is one of the oldest and best-documented Indigenous medicines in South Africa. This bush, which grows wild throughout the sub-Saharan region, smells and tastes like "medicine," thus easily making its way into people's lives and becoming the choice of everyday healing for Xhosa healer-diviners and Rastafarian herbalists. This 'natural' remedy has recently sparked curiosity as scientists search for new molecules against a tuberculosis pandemic while hoping to recognize Indigenous medicine. Laplante follows umhlonyane on its trails and trials of becoming a biopharmaceutical -- from the "open air" to controlled environments -- learning from the plant and from the people who use it with hopes in healing."--Provided by publisher